Improvement of the ergonomical structure of Knapsack sprayer to propel cart sprayer (PCS) - Nordin, Norbaizura; Ahamad Azahari, Ahmad Syakir; Muslim, Maizatul Anis; Kamaruddin, Muhammad Amar (Penerbit UTHM, 2020)
A sprayer is a device used to spray a liquid projection mostly used in agriculture crop used to apply such as pesticides. The sprayer’s usage are based on the type of the background of the farmers scale in agriculture. Large scale of farmers will use the motorize sprayer that will help saving their time to pesticide a large are of corps [1]. Meanwhile, small scale of farmers will use a manual operated sprayer such as Knapsack Sprayer which it is a low cost, low maintenance and easy to use since it does not have engine when operated. Both type of the sprayer has its own advantages and disadvantages that will affect the user. Mainly the manual operated Knapsack Sprayer is a knapsack type, a burden that will make user carry the heavy load at their back while spraying pesticide. The weight of the mixture carried can be up to 17 kilograms depends on the density of the mixture whereas the safe weight lifting legalize by OSHA is 22.68 kilograms which the load almost near to its limit for average man and will affect the body locomotion and bones structure if carried in a long term period. Total sprayed area per full tank are 44.09 meters square [2]. The product that will be made are to counter this problem occur while using Knapsack Sprayer. This product using pushing force to spray the targeted area without having the user to carry a heavy burden while working.